A validated business process modelling success factors model. Issue 5 (7th May 2021) - Bandara, Wasana; Gable, Guy Grant; Tate, Mary; Rosemann, Michael
Abstract : Purpose: Business process modelling (BPMo) projects are core to digital transformation projects as they provide the conceptual foundation to the orchestration of technologies along a process. Yet, success factors of BPMo projects have received little research attention to date. This study empirically validates a BPMo project success model, pointing to normative practice guidelines and important future research. Design/methodology/approach: This research reports on the quantitative re-specification and validation of a business process modelling success model, employing survey responses from 261 process modellers worldwide. Findings: The study distilled and validated a final set of success antecedents: Top Management Support, Project Management Capabilities, Stakeholder Input, Modeller Expertise and Modelling Tool Usage; and clearly evidences their relationships with each other and with two moderating variables – Importance and Complexity. The paper offers a nuanced explanation of the indirect role of top management support in building stakeholder involvement and explains how complex projects that are perceived as important being more likely to attract high levels of necessary stakeholder involvement. The authors conclude that top management needs to create an environment of co-ordinated excellence which spans both technical skills and resources, and a high level of committed engagement between stakeholders and technicians in order for BPMo projects to succeed. Originality/value: This study is the first to operationalize and quantitatively test antecedents of BPMo project success and their interactions, presenting novel insights into how the success factors interact. Awareness of the more influential antecedents of successful process modelling projects offers valuable guidance for the planning, management and conduct of BPMo projects.